2021
DOI: 10.1021/acs.langmuir.0c02837
|View full text |Cite
|
Sign up to set email alerts
|

Proteins and Polyampholytes Interacting with Polyelectrolyte Brushes and Microgels: The Charge Reversal Concept Revised

Abstract: Weak polyampholytes and globular proteins among them can be efficiently absorbed from solutions by polyelectrolyte brushes or microgels even if the net charge of the polyampholyte is of the same sign as that of the brush/microgel. We use a mean-field approach for calculating the free energy of insertion of a probe polyampholyte molecule into a polyelectrolyte brush/microgel. We anticipate that the insertion of the polyampholyte into similarly charged brush/microgel may be thermodynamically favorable due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
(57 reference statements)
0
14
0
Order By: Relevance
“…A more systematic paradigm of charge regulation can be found in simulation studies of synthetic PEs, ampholytes, and artificial peptide sequences. Recently, Laktionov et al used the mean-field theory to show that charge regulation can lead to a charge reversal of ampholytes upon adsorption to polyelectrolyte brushes. Rathee et al have shown that cooperative charge regulation effects account for the association of polyacids with polybases when their p K A values are close to the solution pH, whereas cooperativity vanishes when one or both p K A values are far from the pH .…”
Section: Introductionmentioning
confidence: 99%
“…A more systematic paradigm of charge regulation can be found in simulation studies of synthetic PEs, ampholytes, and artificial peptide sequences. Recently, Laktionov et al used the mean-field theory to show that charge regulation can lead to a charge reversal of ampholytes upon adsorption to polyelectrolyte brushes. Rathee et al have shown that cooperative charge regulation effects account for the association of polyacids with polybases when their p K A values are close to the solution pH, whereas cooperativity vanishes when one or both p K A values are far from the pH .…”
Section: Introductionmentioning
confidence: 99%
“…Following ref. [ 7 ], we present it as where , , , are the respective degrees of ionization of basic and acidic monomer units of type in the globule placed at distance z from the grafting surface or in the bulk of the solution (at ). Because concentration of hydrogen ions in the polyanionic/polycationic brush is larger/smaller than in the bulk of the solution, acidic/basic residues become more strongly/weakly ionized upon insertion of the globule into polyacidic brush and vice versa for the polybasic brush.…”
Section: Resultsmentioning
confidence: 99%
“…Interactions of globular proteins with polyelectrolyte brushes (layers of charged macromolecules end-attached to a planar substrate or to the surface of colloidal particles and immersed in an aqueous solution) have been extensively studied both experimentally [ 1 , 2 , 3 , 4 ] and theoretically [ 5 , 6 , 7 , 8 , 9 , 10 ] in the past two decades.…”
Section: Introductionmentioning
confidence: 99%
“…Block polyelectrolytes with one charged and one hydrophobic block lead to the formation of core-shell micelles where a hydrophobic core is surrounded by a charged polymer corona. This kind of NP allows for the solubilization of hydrophobic molecules, e.g., drugs, in their core while the external shell not only stabilizes them in aqueous media [31,32] but also can bind oppositely charged molecules, e.g., proteins [33][34][35]. On the other hand, random amphiphilic copolymers of polyelectrolyte and hydrophobic monomers, the so called hydrophobically-associating polyelectrolytes, are able to tune viscoelastic properties in aqueous media via a balance between electrostatic repulsions and hydrophobic associative attractions [36,37].…”
Section: Nanoscopic Assembliesmentioning
confidence: 99%